Treatment outcome of sick newborns in primary hospitals in Ethiopia - Efrem Teferi; Ismael Ali; Zergu Tafesse (Jour Med Resh and Health Sci, 2023)
The global neonatal mortality rate has decreased by 37%, per 1000 live births, compared with greater than 50% reduction for mortality rates among children aged 1 to 59 months, since 1990. The main causes of mortality were complications of preterm birth 36%, birth asphyxia 23%, and infections 23%. In Ethiopia neonatal mortality decreased from 39 to 29 between the 2005 and 2016 EDHS but has remained stable since the 2016 EDHS.